Analisis Persepsi Civitas Akademika Terhadap Konsep Merdeka Belajar Menyongsong Era Industri 5.0 - Lestiyani, Pudji (Jurnal Kependidikan : Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran, dan Pembelajaran, 2020)
This study aims to recognize the understanding of the concept â€œMerdeka Belajarâ€ and the Industry Revolution 5.0 and the readness of educational actors in facing the Industry Era 5.0. The method used in this research was descriptive qualitative involving educational actors, 50 teachers, 100 students, and 100 parents as participants. The instruments used in data collection were observation, closed interviews, and questionnaires. The data analysis technique was carried out by analyzing the data obtained through the research instruments. The results of the study showed that not all education actors understood the concept of â€œMerdeka Belajarâ€ and the Industry Era 5.0. Mastery and utilization of ICT was low andÂ needed to be improved. Educational actors, especially in secondary education must prove that the independence of learning provided by the government was able to form excellent human resources who are ready to face the Industry Era 5.0. These human resources involves professionalism, competitive power, functional competence, participatory advantage, and collaboration.